APLIKASI UJIAN TENGAH SEMESTER DAN AKHIR SEMESTER PADA UNIVERSITAS JABAL GHAFUR BERBASIS ANDROID - Rachmad Nurhaqi Akbar (KIRANA : Social Science Journal, 2024)
Midterm and final semester exams at Jabal Ghafur university are a method used to evaluate student learning outcomes in measuring the level of academic achievement of students as students, so that students can know their own limits in understanding the field of study pursued while attending education by implementing exams using internet, where students and lecturers do not have to meet face to face during the exam. Along with the development of advances in information technology, it might be greatly helped by the existence of an Android-based application. With an Android-based application, we will easily provide services that can be accessed from anywhere and at any time to be able to access information with only a mobile phone with the Android operating system. Making an android application using the Android Studio application with the Java and XML programming languages ​​so as to produce an Android-based APK which is currently very much needed to facilitate the process of student examinations and assessments. Data storage uses MySQL so that it is more secure and can provide fast information. So that the process of student examinations and assessments can be processed more easily and produce data that is fast, precise and accurate.